1990
DOI: 10.1111/j.1745-4565.1990.tb00047.x
|View full text |Cite
|
Sign up to set email alerts
|

OXYRASETM ENZYME AND MOTILITY ENRICHMENT FUNG‐YU TUBE FOR RAPID DETECTION OF LISTERIA MONOCYTOGENES AND LISTERIA SPECIES1

Abstract: A rapid and simple method using a U‐shaped glass apparatus (Fung‐Yu tube) for early determination of the presence of Listeria monocytogenes and Listeria species in mixed cultures and inoculated meat samples has been developed. This system utilizes unique biochemical and physical properties of Listeria for selective enrichment. Fraser broth was used as a selective enrichment broth especially for observation of esculin hydrolysis (blackening of broth), and semisolid Modified Oxford agar was used for selective de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…tested, except Salmonella typhimurium and Proteus vulgaris grew more rapidly and to a higher turbidity in Oxyrase supplemented broths than in controls. Our results add to the findings of Yu (1991), i.e., Oxyrase provides microaerobic conditions for growth of both facultative anaerobes and microaerophilic…”
Section: Dose Response Of Campylobacter Strains To Oxyrasetmsupporting
confidence: 87%
See 1 more Smart Citation
“…tested, except Salmonella typhimurium and Proteus vulgaris grew more rapidly and to a higher turbidity in Oxyrase supplemented broths than in controls. Our results add to the findings of Yu (1991), i.e., Oxyrase provides microaerobic conditions for growth of both facultative anaerobes and microaerophilic…”
Section: Dose Response Of Campylobacter Strains To Oxyrasetmsupporting
confidence: 87%
“…Time in hours after incubation in a 42 C gyrotory water bath shaker (100 gyrationshin) of Listeriu, and reported that Oxyrase was more beneficial to the slower growing strains.The effect of Oxyrase on growth of facultative anaerobes in nonselective broth media was studied byYu (1991). She showed that all of the facultative anaerobes…”
mentioning
confidence: 99%
“…from other organism5 by development of a black color. Yu and Fung (1991 ) and Fung and Yu (1993) reported that the use of Fraser broth containing a membrane fraction (Oxyrase) in association with modified Oxford agar (MOX) in the Fung-Yu U-shaped tube. This system enables rapid detection of Listeriti r,iorioc'!…”
Section: Introductionmentioning
confidence: 99%
“…It creates anaerobiosis in a variety of bacteriological media. The activity of the membrane fraction is due to the presence of an active cytochrome-based electron transport system (Yu and Fung 1991). Tuitemwong (1993) reported that membrane fractions derived from Escherichia coli E-8 and acetic acid bacteria demonstrated oxygen-scavenging activities equivalent to that of Oxyrase in a buffer solution and in yogurt and buttermilk mixes.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, selective methods for campylobacter isolation are involved which are time consuming. A method has been developed (Yu and Fung 1991;Yu and Fung 1992) for isolation of certain bacteria involving the use of the membrane bound oxyrase enzyme system of Escherichiu coli as a media supplement. They found that by using oxyrase in the media, special atmospheric conditions were not needed.…”
Section: Introductionmentioning
confidence: 99%